2021
DOI: 10.21608/ajps.2021.153568
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Relation of Urinary Tract Infection Bacterial Pathogens to Sex and Ages Among Patients in Three Arab Countries

Abstract: Background: urinary tract infections is one of the most prevalent bacterial infections worldwide. The present study aims to study and survey different isolates from urine specimens from different countries to assess their prevalence and their relation to urinary tract infections. One hundred and sixty-eight samples were randomly collected from three countries, Egypt, Sudan and Saudi Arabia, as follows: 43, 33 and 92, respectively. Samples were collected from private laboratories and from both sexes. The ages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The results of this study showed that E.coli bacteria is one of the most members of the enteric family that causes about 81.4% of urinary tract infections followed by Klebsiella pneumonia about 10.26 %. This is consistent with those obtained by (Azab, 2021) and Jawetz et al, (2016), they reported that E.coli have been found to be the most common causative organism of UTI in many countries followed by K. pneumonia and even globally, E.coli is the most common pathogen causing UTIs, it causes 80-85% of cases. Three G -ve E.coli species were selected from the three infection levels mentioned in Table (1).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that E.coli bacteria is one of the most members of the enteric family that causes about 81.4% of urinary tract infections followed by Klebsiella pneumonia about 10.26 %. This is consistent with those obtained by (Azab, 2021) and Jawetz et al, (2016), they reported that E.coli have been found to be the most common causative organism of UTI in many countries followed by K. pneumonia and even globally, E.coli is the most common pathogen causing UTIs, it causes 80-85% of cases. Three G -ve E.coli species were selected from the three infection levels mentioned in Table (1).…”
Section: Discussionsupporting
confidence: 92%
“…In younger children (6-12 years old), there may be less gender-specific behaviors or activities that increase the risk of UTIs. However, as children reach adolescence (>12-14 years old), factors such as sexual activity or hygiene practices may play a role in the higher rate of UTIs in females [27]. Male and female immune responses differ, especially throughout puberty, which could account for some of the reported variations in UTI incidence [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is an important cause of community-acquired and health care-associated infections, including those involving the urinary tract (46%), surgical wound (24%), lower respiratory tract (30%) and the bloodstream (17%) itself [10]. It is also a common cause of complicated urinary tract infections (UTIs) in patients with anatomical or functional problems [11]. The use of fosfomycin has attracted renewed interest for the treatment of serious systemic infections caused by multidrug-resistant Enterobacteriaceae [12].…”
Section: Introductionmentioning
confidence: 99%